Modeling flow in anisotropic porous medium with full permeability tensor. (October 2019) - Cao, Jie; Gao, Hui; Dou, Liangbin; Zhang, Ming; Li, Tiantai
Abstract: The flow in anisotropic porous medium is significant for the modeling of subsurface fluids transportation. The subsurface porous medium is usually both heterogeneous and anisotropic, caused by the compaction and sedimentations effects on the formation. Full permeability tensor is therefore needed in modeling flow in anisotropic medium. In this research, two widely used finite volume schemes, Two-Point Flux Approximation (TPFA) and Multi-Point Flux Approximation (MPFA), are applied to solve the flow model with a full permeability tensor. The results verified that ignoring anisotropy of the porous medium results in overestimation of the total flux. The TPFA methods have high computational efficiency, but failed to represent the anisotropy. The MPFA scheme takes more CPU time than TPFA for same grid block resolution, but incorporates the anisotropy using a full tensor. The comparison between the results from two methods indicates that ignoring anisotropy results in significant errors in determined flux.